Barbershop Service Booking on Application for Hair Emotion Matrix Saloon - Cheong, Wai Feng; Saringat, Mohd Zainuri (Applied Information Technology And Computer Science, 2023)
The Booking Barber Service System is a system which managing customer reservations. The purpose of developing this system is to solve the problem of when there are too many customers coming at one time, which result shopkeepers becoming less focused on service quality. This system accepts barber services from customers and these service information will be gathered and display to the barber and owner. Prototype methodology is selected for this system throughout the project system development life cycle. The development of system are using object-oriented that emphasizes object methods as opposed to a structured approach that uses procedural methods. The system was develop by using Android Studio with JAVA and Firebase programming. Through this application, the systematic booking process can overcome the problem of waiting time and improve the quality of service as well as better business data management.